Agency Leaders' Assessments of Feasibility and Desirability of Implementation of Evidence-Based Practices in Youth-Serving Organizations Using the Stages of Implementation Completion - Lawrence A. Palinkas; Mark Campbell; Lisa Saldana (Frontiers Media S.A., 2018)
Background: This study examined influences on the decisions of administrators of youth-serving organizations to initiate and proceed with implementation of an evidence-based practice (EBP).Methods: Semi-structured interviews, developed using the Stages of Implementation Completion (SIC) as a framework, were conducted with 19 agency chief executive officers and program directors of 15 organizations serving children and adolescents.Results: Agency leaders' self-assessments of implementation feasibility and desirability prior to implementation (Pre-implementation) were influenced by intervention affordability, feasibility, requirements, validity, reliability, relevance, cost savings, positive outcomes, and adequacy of information; availability of funding, support from sources external to the agency, and adequacy of technical assistance; and staff availability and attitudes toward innovation in general and EBPs in particular, organizational capacity, fit between the EBP and agency mission and capacity, prior experience with implementation, experience with seeking evidence, and developing consensus. Assessments during the Implementation phase included intervention flexibility and requirements; availability of funding, adequacy of training and technical assistance, and getting sufficient and appropriate referrals; and staffing and implementing with fidelity. Assessments during the Sustainment phase included intervention costs and benefits; availability of funding, support from sources outside of the agency, and need for the EBP; and the fit between the EBP and the agency mission.Discussion: The results point to opportunities for using agency leader models to develop strategies to facilitate implementation of evidence-based and innovative practices for children and adolescents. The SIC provides a standardized framework for guiding agency leader self-assessments of implementation.